Capital Punishment in Summary Proceeding (Archives of Criminology, 2008)
The author of this article takes an in-depth look at capital punishment in Poland under the summary execution procedure, using a selected example. For this purpose, he introduces a famous case (ref. IVK dor. 24/83), which was examined in a summary procedure by the Voivodship Court in Warsaw and as a result of which one of the perpetrators was finally sentenced to 25 years’ imprisonment and the other to the death penalty. Andrzej Rzepliński emphasises that the example under discussion was the most important trial on the death penalty in Poland at the time when the provisions of the 1969 Penal Code were in force. The article also discusses data relating to provincial courts that renounced the death penalty in the period of 1970 to 1998. The article then describes the crime committed by the two defendants and their profiles. In addition, it includes a profile of the victim and, most importantly, an in-depth analysis of the trial itself. It also contains an in-depth look at the punishment that was meted out to the perpetrators. The author describes at length the conduct and voting of the judges responsible for the verdict, the course of the unsuccessful proceedings to pardon one of the perpetrators, his 108-day stay on death row, and his execution. The study also includes a description of the social reception and media coverage of the case, which the author based on a survey of the newspapers and periodicals that appeared in the year of the execution. In conclusion, Rzepliński notes the insufficiently justified decision of the judges to hand down the sentence of imprisonment to one convict and of death to the other. He also draws attention to the fact that those dispensing justice are fallible, and that if they impose the death penalty, they have no opportunity to remedy the consequences of their error.